2005
DOI: 10.1073/pnas.0409024102
|View full text |Cite
|
Sign up to set email alerts
|

Breaking sieve for steric exclusion of a noncognate amino acid from active site of a tRNA synthetase

Abstract: The genetic code is fixed in aminoacylation reactions catalyzed by aminoacyl-tRNA synthetases. Amino acid discrimination occurs at two sites: one for amino acid activation and aminoacylation and one for editing misactivated amino acids. Although the active site sieves out bulkier amino acids, misactivation occurs with substrates whose side chains are smaller than the cognate one. Paradoxically, although alanyl-tRNA synthetase activates glycine as well as alanine, the sterically larger (than alanine) serine is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…39 Analysis of the structures of Staphylococcus aureus threonyl-tRNA synthetase bound to ATP and Zn 2+ and to an adenylate analogue (threonyl-AMS) and the structures of the MgATP and alanine complexes of A. aeolicus alanyltRNA synthetase supports this common binding mode in class II tRNA synthetases. 40,41 The structure of the AaBPL:biotin:ATP complex has revealed the importance of Arg40 from the glycine-rich motif in the stabilisation of the two ligands. The side chain of this conserved arginine plays an important role in the neutralisation of the negative charges of the triphosphate chain of ATP as well as positioning the biotin carboxylate in close proximity to the α-phosphate.…”
Section: Resultsmentioning
confidence: 99%
“…39 Analysis of the structures of Staphylococcus aureus threonyl-tRNA synthetase bound to ATP and Zn 2+ and to an adenylate analogue (threonyl-AMS) and the structures of the MgATP and alanine complexes of A. aeolicus alanyltRNA synthetase supports this common binding mode in class II tRNA synthetases. 40,41 The structure of the AaBPL:biotin:ATP complex has revealed the importance of Arg40 from the glycine-rich motif in the stabilisation of the two ligands. The side chain of this conserved arginine plays an important role in the neutralisation of the negative charges of the triphosphate chain of ATP as well as positioning the biotin carboxylate in close proximity to the α-phosphate.…”
Section: Resultsmentioning
confidence: 99%
“…3a and b), as observed in all of the class II aaRS structures. 16,19,23,[25][26][27]31,38,41 The structure of the present apo form of PylRS(c270) was compared with that of the AMPPNP-bound form, to reveal the ATP-induced conformational changes. Although the overall structures were essentially the same (rmsd of the C α carbon atoms of 0.59 Å over 254 residues), the apo The residues that move significantly upon AMPPNP binding, Asn280, Asp281, Thr282, Glu283 (the ordering loop) and Asp334, Gly335, and Lys336 (the motif-2 loop), are colored vermilion and green, respectively.…”
Section: Atp-induced Conformational Changesmentioning
confidence: 99%
“…The inclusion of noncognate serine and glycine in the AlaRS activation site was reported in ref. 10 and was recently confirmed structurally (11). The structures of AlaRS complexed with amino acids suggested that serine hydroxyl is accommodated by an induced fit of Asn-194 that allows expansion of the activation pocket and that the smaller glycine is also included, based simply on a canonical size-sieving model.…”
mentioning
confidence: 90%